ÉTICA Y RESPONSABILIDAD JURIDICA EN LAS ORGANIZACIONES EMPRESARIALES - Ugarte Vega Centeno, Máximo Alfredo (2008)
The change of century has brought new demands in the economy, the technology and even, the use of the Internet, the ones that have accentuated the disclosure of the know-how and the increment of the social role of the businesses in the advance of the organizations, as well as its growing role in the societies. It is there where arises the ethics as responsibility in the organizations, with regard to the transparency of the business conducts that benefit all the community and to the same business, besides avoiding the juridical-legal consequences that would involve their not practical use.